Nanotechnology in food production: a comprehensive bibliometric analysis using R-package - Rajendran, Salini Devi; Wahab, Siti Norida; Yeap, Swee Pin; Kamarulzaman, Nitty Hirawaty; Abdul Halim Lim, Sarina (EManuscript Technologies, 2023)
Nanotechnology’s advent and development present an excellent potential to improve the complicated technical issues that food production necessitates. It may bring revolutionary changes to the food production system in the future years. Thus, the goal of this study is to present the current state of nanotechnology in food production. Furthermore, the authors characterize the primary subjects in this study stream, highlight future research potential, and propose a future research plan. This study conducted a bibliometric analysis using data from the Scopus database. The authors are able to retrieve 426 documents for the analysis based on the keywords chosen. The frequency analysis was done using Microsoft Excel, and the citation metrics and analysis were done using R-package software. The findings of this study are reported using standard bibliometric indicators including source title, source type, document type, publication year, subject area, languages, keywords analysis, authorship, citation analysis, geographical distribution, and active institutions. According to our findings, the number of publications on nanotechnology in food production has increased dramatically since 2003. The growing number of studies on nanotechnology demonstrates the relevance of technology in the food sector, which could have implications for the environment, economy, and society.